2005
DOI: 10.1007/s10165-005-0418-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison in values of color flow signals and vascular resistance of synovial vascularity demonstrated by Doppler sonography between knee and metacarpophalangeal joints of patients with rheumatoid arthritis

Abstract: Synovial vascularity of 12 patients with rheumatoid arthritis (RA) was examined by Doppler sonography for color flow signals and vascular resistance on knee joints and metacarpophalangeal (MCP) joints, and the results were compared with each other and with C-reactive protein (CRP) levels of the patients. A significant correlation was observed between knee resistance index (RI) and MCP-RI (P = 0.0140), but not between knee color flow signals and MCP color flow signals (P = 0.1029). A significant correlation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2006
2006
2008
2008

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…The results that the difference (beforeafter) values did not correlate between CFS and values of CRP, ESR, and DAS28-E3 could indicate a lower association of CFS with these clinical factors. The present lower frequency of positive CFS in MCP joints (39%) may also be responsible for the lack of significant correlation between RI values of knee and MCP joints, in contrast to the significant correlation (P < 0.01) between knee-RI and MCP-RI observed in the previous study, 8 because a higher frequency of positive CFS in MCP joints (54%) was observed in the previous study. The present significant correlation between CFS and RI values in both knee and MCP joints is consistent with results of previous studies scanned on knee joints.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The results that the difference (beforeafter) values did not correlate between CFS and values of CRP, ESR, and DAS28-E3 could indicate a lower association of CFS with these clinical factors. The present lower frequency of positive CFS in MCP joints (39%) may also be responsible for the lack of significant correlation between RI values of knee and MCP joints, in contrast to the significant correlation (P < 0.01) between knee-RI and MCP-RI observed in the previous study, 8 because a higher frequency of positive CFS in MCP joints (54%) was observed in the previous study. The present significant correlation between CFS and RI values in both knee and MCP joints is consistent with results of previous studies scanned on knee joints.…”
Section: Discussioncontrasting
confidence: 85%
“…Doppler sonographic scanning of MCP and knee joints has been performed to examine correlation between color flow signals (CFS) and resistance index (RI) of synovial vascularity in MCP and knee joints. 8 However, there have been no reports of scanning of MCP and knee joints simultaneously for evaluation of TNF-伪 blockades.…”
Section: Introductionmentioning
confidence: 99%
“…This study also found a significant inverse correlation between RI and fl ow signal intensity, which others and we have previously reported. [16][17][18][19][20] Taken together, the results of the present study suggest that the degree of synovial effusion had a stronger association with the increased grades of fl ow signals which have higher perfusion (lower RI values) and are located in the superfi cial layer of the pannus, whereas pannus thickness had a stronger association with the larger vessels which have lower perfusion (higher RI values) and are located in the deep layer of the pannus.…”
Section: Color-fl Ow Signals and Rimentioning
confidence: 49%